PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN PELECEHAN SEKSUAL MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 - Widya, Sri; Iskandar, Hadi; Yusrizal, Yusrizal (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
This study aims to examine how legal protection of children as victims of sexual abuse according to Law Number 35 of 2014, as well as how criminal liability perpetrators of sexual abuse against children. The government has implemented two laws, Law No. 23 of 2004 and Law No. 35 of 2014, with the main aim of protecting children. However, despite legal action, there are still cases of sexual abuse such as sexual abuse against children still occur in schools, neighborhoods, or in the family environment. This research uses normative research using a statutory approach and a conceptual approach, legal norms or or rules. Based on the results of research that the regulation that specifically regulates the protection of children, namely Law No. 35, 2014 relates to the Amendment of Law No. 23, 2002 concerning Child Protection, which is a legal instrument that can protect children from criminal acts, including sexual abuse. This law stipulates that sexual cruelty to children is cruelty, so that suspects can be brought to the police with the support of related individuals, there are also sanctions for perpetrators of sexual abuse violence against children, which is quite concise 5 years and quite late 15 years in prison and also compensation. And the suspect of sexual abuse of children must be accountable for all his actions before the law and must receive appropriate punishment in line with applicable rules and regulations and also he will be subject to compensation.